Digital Competence and Adaptability: Keys to Career Readiness in the Era of Artificial Intelligence - Ira Puspitadewi S; Septy Holisa Umamy (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research aims to determine the influence of Digital Competence and Adaptive Capability on the Career Readiness of Students at the Faculty of Economics and Business. The population of this research was 372 students from the Faculty of Economics and Business with a sample size of 79 using the Slovin formula with purposive sampling technique. This research is quantitative descriptive. The data collection method in the research uses primary data, namely questionnaires via form and secondary data. The data analysis technique uses multiple linear regression analysis with SPSS software ver 25. Based on the findings, it shows that partially the Digital Competence variable and the Adaptive Capability variable have an effect on Career Readiness. And simultaneously the Digital Competence and Adaptive Capability variables on Career Readiness in students at the Faculty of Economics and Business. This linear regression model with independent variables (Digital Competence and Adaptive Capability), has proven to be very effective in explaining the dependent variable (Career Readiness) because it approaches the value of one (1). These findings provide an important contribution in designing more effective curriculum development strategies to improve student career readiness in the digital era.